Cross-borehole GPR survey for the study of the grouting - Pant, SR (Journal of Nepal Geological Society, 2008)
To check the effectiveness of the grouting in the Flip Bucket Area, Spill Way, Damsite of Middle Marsyangdi Hydroelectric Project cross-borehole ground penetrating radar (GPR) tomography survey was carried out. The test was carried out in two pairs of boreholes. The first pair was BH-1 and BH-2 and the second pair was BH-3 and BH-4. Second pair of boreholes was taken as model site. In the first pair of boreholes BH-1 and BH-2 cross borehole GPR tomography survey was conducted before grouting and after grouting. Before grouting measurement was carried out on June 11, 2006 and after grouting measurement was carried out on June 28-30, 2006 and September 25-26, 2006. The measurement in the pair of model boreholes BH-3 and BH-4 was carried out in June 29-30, 2006. The data acquisition method adapted was Zero Offset Profiling (ZOP) and Multiple Offset Gathering (MOG). The Observation interval was 25 cm. The antenna centre frequency used was 200 MHz. The distance between the pair of boreholes BH-1 and BH-2, BH- 3 and BH-4 was 6 m. In cross-borehole GPR tomography measurement of the arrival time of waves are carried out with high accuracy. Propagation of the GPR waves linearly depends on the porosity (water filled) and the chemistry (electrical conductivity) of the water: higher the porosity slower the velocity and higher the electrical conductivity greater the attenuation of the GPR waves. So, GPR tomograms can be used to quantify the subsurface. The results of the investigation were useful to know the subsurface before and after the grout injection. Before grouting the porosity of the fractured rocks between the pair of boreholes BH-1 and BH-2 was between 15% to 20%. This value is low in comparison with porosity of granular material. In principle GPR monitoring of grout study should be much more effective for high porosity formation. Between the pair of boreholes BH-1 and BH-2 grouting is effective below the depth of around 7.5 m. The September monitoring indicates that the GPR wave velocity has been increased in the most part of the subsurface from 0.10 m/ns to 0.11 m/ns at depth greater than 7.5 m. In this zone porosity has also been reduced. There is no clear evidence of the change in the physical parameters (velocity, porosity and electrical conductivity) at depth less than 7.5 m and between 18 m and 20 m. This may be due to the high velocity of the groundwater flow in these zones. The velocity between the pair of model boreholes BH- 3 and BH-4 is greater than 0.11 m/ns. In this model site porosity is less than 12% and the predominant value of porosity is around 10%. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.16